Vaginal Microbial Environment Skews Macrophage Polarization and Contributes to Cervical Cancer Development - Guannan Zhou; Fangyue Zhou; Yuanyuan Gu; Menglei Zhang; Ganrong Zhang; Fang Shen; Keqin Hua; Jingxin Ding (Journal of Immunology Research)
As a common female reproductive system malignancy, cervical cancer (CC) disturbs numerous women’s health. This study demonstrates the role of the vaginal microbial environment (Peptostreptococcus anaerobius) in cervical cancer. Functional assays, including cell proliferation assay, tube formation assay, and immunofluorescence staining, revealed the effect of Peptostreptococcus anaerobius-treated macrophages on cell proliferation and the angiogenesis process. The tube formation assay disclosed the function of Peptostreptococcus anaerobius-treated macrophages on angiogenesis. In vivo assays were also established to explore the impact of Peptostreptococcus anaerobius-treated macrophages on tumor migration. The results revealed that Peptostreptococcus anaerobius-induced macrophages boosted cervical cancer migration and angiogenesis both in vitro and in vivo. Then, this study unveiled that Peptostreptococcus anaerobius-induced macrophage secreted VEGF to stimulate the angiogenesis in cervical cancer. As a whole, Peptostreptococcus anaerobius-induced macrophage facilitates cervical cancer development through modulation of VEGF expression.